2005
DOI: 10.3138/cjccj.47.3.527
|View full text |Cite
|
Sign up to set email alerts
|

Can Mediation Be Therapeutic for Crime Victims? An Evaluation of Victims' Experiences in Mediation with Young Offenders

Abstract: Victims' experiences in the justice system may help or hinder their healing process. Restorative justice aims to heal the suffering caused by victimization (Zehr 2002). However, some victim advocates have expressed concern that restorative justice may augment victims' suffering. This article presents the results of an evaluation of the experiences of crime victims who were invited to participate in a mediation program. Using therapeutic jurisprudence as a framework, the study looks at how victims' fear was aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 10 publications
0
56
0
1
Order By: Relevance
“…Shapland et al (2006), who studied almost 300 restorative conferences with adult offenders, note that the likelihood of conference breakdown and dissatisfaction among victims increased if an offender even partially denied responsibility for the harm. Based on the results of their interviews with 59 victims, Wemmers and Cyr (2005) theorize that victims may experience re-traumatization through a restorative justice process if the offender denies responsibility for the event. Petrucci (2002) proposed attribution theory to explain that the offender's assumption of responsibility for the harm allows the victim to cease destructive self-blaming.…”
Section: Evaluative Strategymentioning
confidence: 99%
“…Shapland et al (2006), who studied almost 300 restorative conferences with adult offenders, note that the likelihood of conference breakdown and dissatisfaction among victims increased if an offender even partially denied responsibility for the harm. Based on the results of their interviews with 59 victims, Wemmers and Cyr (2005) theorize that victims may experience re-traumatization through a restorative justice process if the offender denies responsibility for the event. Petrucci (2002) proposed attribution theory to explain that the offender's assumption of responsibility for the harm allows the victim to cease destructive self-blaming.…”
Section: Evaluative Strategymentioning
confidence: 99%
“…Several evaluation studies have reported that although many victims were satisfied with the way their case was dealt with, a smaller number of victims showed dissatisfaction or felt re-victimized after RJ practices (Morris & Maxwell, 1997;Strang, 2002;Wemmers, 2002;Wemmers & Cyr, 2005). Although the reasons varied and some were attributed to offenders' attitudes and behaviors rather than practices (Daly, 2003b;Gerkin, 2008), one of the most common reasons given for negative outcomes was lack of care and attention toward victims, such as lack of preparation for victims (Choi & Gilbert, 2010;Umbreit, Vos, Coates, & Lightfoot, 2005) or excessive focus on offenders Strang, 2002).…”
Section: Paradox Of Institutionalization Of Rj Practicesmentioning
confidence: 99%
“…Victims thus have no opportunity to present their own account of past events, but are instead confined to answering questions within the parameters set down by the questioner. Cross-examination, in particular, has been found to be highly anti-therapeutic (Wemmers & Cyr, 2005) and particularly injurious to the psychological well-being of victims and witnesses; particularly children and complainants in cases of rape and sexual assault (Doak, 2008).…”
Section: Account-makingmentioning
confidence: 98%